Sub-Regional Differences of the Human Amniotic Membrane and Their Potential Impact on Tissue Regeneration Application - Weidinger, Adelheid; Poženel, Laura; Wolbank, Susanne; Banerjee, Asmita (Frontiers in Bioengineering and Biotechnology, 2021)
For more than 100 years, the human amniotic membrane (hAM) has been used in multiple tissue regeneration applications. The hAM consists of cells with stem cell characteristics and a rich layer of extracellular matrix. Undoubtedly, the hAM with viable cells has remarkable properties such as the differentiation potential into all three germ layers, immuno-modulatory and anti-fibrotic properties. At a first sight, the hAM seems to be one structural entity. However, by integrating its anatomical location, the hAM can be divided into placental, reflected and umbilical amniotic membrane. Recent studies show that cells of these amniotic sub-regions differ considerably in their properties such as morphology, structure, and content/release of certain bioactive factors. The aim of this review is to summarize these findings and discuss the relevance of these different properties for tissue regeneration. In summary, reflected amnion seems to be more immuno-modulatory and could have a higher reprogramming efficiency, whereas placental amnion seems to be pro-inflammatory, pro-angiogenic, with higher proliferation and differentiation capacity (e.g. chondrogenic, osteogenic), and could be more suitable for certain graft constructions. Therefore, we suggest that the respective hAM sub-region should be selected in consideration of its desired outcome. This will help to optimize and fine-tune the clinical application of the hAM.